PENINGKATAN PRODUKSI DAN MUTU BUAH ANGGUR DENGAN PEMBERIAN IRIGASI TETES DAN PUPUK MINERAL PLUS PADA LAHAN KERING KECAMATAN GEROKGAK, BULELENG - MERIT, I NYOMAN; NARKA, IWAYAN; BHAYUNAGIRI, IDA BAGUS PUTU (Agrotrop : Journal on Agriculture Science, 2012)
Increasing the Production and Quality of Grape Yield with Drip Irrigation and Mineral Plus Fertilizer. The aim of this research was to find out the optimum of irrigation intervals and mineral plus fertilizer application in order to increase the production and quality of grape yield. The research was set up for two years program. In the first year, the observation was focused on vegetative growth while yield production was observed in the second year. Three intervals of irrigation viz 2, 4 and 6 days and mineral plus fertilizer dose (M , M 0 and M ) was tested in nested randomized block design with three replications. Parameter of vegetative growth such as plant height, stem diameter and number of branch was measured regularly. Supporting parameters such as soil moisture content, soil water potential, plant water status as indicated by relative water content (RWC) was also measured. In the second year, the production and quality of yield such as number of bunch per plant, number of fruit per bunch and sugar content of fruit were measured. The results showed that mineral plus fertilizer gave a significant effect on grape production, both in first and second harvest. Total yield production of first and second harvest of treatment M0, M1 and M2 was 23.63 kg 27.95 kg and 30.81 kg, respectively. The yield was increased of 18.28 % and 30.38 % of M1 and M2 compare to M0. Interval water supply, has a significant effect on grape yield both in first and second harvest. Total yield production of I1, I2 and I3 was 33.04 kg, 28.18 kg and 21.17 kg, respectively. This was decreased of about 14.71% and 35.93% of I2 and I3 compare to I1. Yield quality was increased as mineral fertilizer increased. Sugar content, volume of seed and respondent that mentioned the yield was sweet, significantly increased as mineral plus fertilizer increased
Keywords: drip irrigation, grape, mineral fertilizers